1997
DOI: 10.1046/j.1365-2605.1997.t01-1-00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐glucosidase activity in the rat epididymis under different physiological conditions

Abstract: The estimation of alpha-glucosidase activity in semen is widely used as a marker of epididymal function. In the present studies, glucosidase activity was evaluated in the different segments of the rat epididymis under various physiological conditions. In addition, the effect of two known male antifertility agents, gossypol and alpha-chlorohydrin, on enzyme activity was evaluated. Enzyme activity was absent from the epididymis of rats aged 10 and 20 days but became detectable at 30 days of age when the adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…One study showed that NAG levels are lower in the seminal plasma of patients with severe oligozoospermia or epididymal pathologies [17], possibly as a result of lower testicular testosterone levels. Testosterone is necessary for the function of the epididymis [29], as was shown by a study in rats, in which NAG activity was reduced significantly in all segments of the epididymis 7 days after castration [30]. Previous studies show that NAG activity is positively correlated with traditional semen variables [17, 29,31,32], and are consistent with the results of the present study, which suggest that a normal secretion of this epididymal marker is associated with semen quality.…”
Section: Discussionsupporting
confidence: 92%
“…One study showed that NAG levels are lower in the seminal plasma of patients with severe oligozoospermia or epididymal pathologies [17], possibly as a result of lower testicular testosterone levels. Testosterone is necessary for the function of the epididymis [29], as was shown by a study in rats, in which NAG activity was reduced significantly in all segments of the epididymis 7 days after castration [30]. Previous studies show that NAG activity is positively correlated with traditional semen variables [17, 29,31,32], and are consistent with the results of the present study, which suggest that a normal secretion of this epididymal marker is associated with semen quality.…”
Section: Discussionsupporting
confidence: 92%
“…ACH is well known to inhibit the activity of G3PDH, one of the glycolytic enzymes that interferes with epididymal sperm maturation [10,14]. In our study, the transcript of G3PDH was remarkably down-regulated by ACH, and some other enzymes associated with the glycolytic pathway were also inhibited.…”
Section: Discussionsupporting
confidence: 58%
“…Other findings suggested that ACH can affect epididymal function through multiple pathways, including inhibiting androgen dependent enzymes such as ATPase and AChE in the epididymis [11], influencing some markers involved in epididymal function such as glucosidase activity, acid and alkaline phosphatase activity, and sialidase activity [12-14], regulating the epididymal microenvironment such as acidity, fluid resorption and salt metabolism [15,16], and interfering with sugar transport, lipid metabolism and epididymal protein secretion [17-19]. All of the above effects on epididymal function through ACH indicate that it may influence male fertility by interfering with the epididymal milieu, in which the spermatozoa mature, rather than directly affecting spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The ALP levels did not differ between the control and treated groups, suggesting normal functioning of the prostate. The activity levels of α -glucosidase, a marker for epididymal sperm maturation [28], and lactic acid another important seminal plasma constituent of seminal vesicle [27] were also analyzed and remained unchanged, suggesting normal synthesis of seminal plasma constituents by the accessory reproductive organs after Nisin treatment.…”
Section: Discussionmentioning
confidence: 99%